PENGARUH LITERASI AKUNTANSI TERHADAP PERENCANAAN KEUANGAN SISWA SMAK YOS SUDARSO KEPANJEN - Mbipi, Saverius Dhuri (Fakultas Ekonomi Universitas Wisnuwardhana, 2025)
This research aims to analyze the influence of accounting literacy on students' financial planning. Accounting literacy includes students' understanding of basic accounting concepts, budget management, and the ability to record finances simply. Financial planning is an important competency for students to face economic challenges in the future. This research uses a quantitative approach with a survey method, involving high school/vocational school students as respondents. The results of the analysis show that accounting literacy has a significant influence on students' ability to prepare effective financial plans. Students with a good level of accounting literacy tend to be better able to manage pocket money, set financial priorities, and set aside funds for future needs. These findings emphasize the importance of integrating accounting literacy in the school curriculum to increase students' financial awareness and skills. Thus, increasing accounting literacy can be a strategic step in forming a financially intelligent generation.